Plan de desarrollo y ordenamiento territorial de la parroquia Chuquiribamba perteneciente al cantón Loja. - Montaño Ordóñez, Julio Alexander (2011)
The Territorial Ordering is constituted in a process of planning of technical-political character through as it is formed in short, medium and long term, an organization of the use and occupation of the territory, agreed with the potentialities and limitations of itself, the expectations and limitations of the population and the sectorial objectives of development (economic, social, cultural and ecological) and whose management is within the National Plan the Good one To live, in the National Territorial Strategy of Ecuador and with base in the competitions that the Constitution assigns to the decentralized independent governments to parochial level; they allowed that the present work will focus in the elaboration of a Plan of Development and Territorial Ordering (PDOT) for the Chuquiribamba Parish pertaining to the Loja Corner, the same one that is possessing of a great ethnic, social, cultural and natural wealth, which has come suffering by the great political changes - economic that take place at national level, by the inadequate infrastructures that maintain, the form in how these have been located and the problems that these cause to the atmosphere and the society. With the present work the identification of seven zones or communities of study was obtained: Center of Chuquiribamba (the Painful one), District the Pordel, District San Vicente, Huiñacapac District, Simon District Bolivar, Tesalia District, Zañi District; by means of the diagnosis of the systems: ecological, economic, of slumbers, mobility and connectivity, cultural partner, and of management of the territory; being in the proposal of the lineaments for the Plan of Territorial Ordering of Chuquiribamba like: To promote the citizen participation through social organizations with the purpose of creating identity with respect to the coexistence with the patrimony, promoting specific studies to microzonificar areas in: seismic, load, pressure litostática and geotechnical to determine zones of threats and vulnerability, and to be able to regulate the troop density in urban grounds, among others. And that will have to be taken in consideration by the local and national authorities.